Polygyny, mate-guarding, and posthumous fertilization as alternative male mating strategies - Zamudio, Kelly R. (The National Academy of Sciences, 2000)
Alternative male mating strategies within populations are thought to be evolutionarily stable because different behaviors allow each male type to successfully gain access to females. Although alternative male strategies are widespread among animals, quantitative evidence for the success of discrete male strategies is available for only a few systems. We use nuclear microsatellites to estimate the paternity rates of three male lizard strategies previously modeled as a rock-paper-scissors game. Each strategy has strengths that allow it to outcompete one morph, and weaknesses that leave it vulnerable to the strategy of another. Blue-throated males mate-guard their females and avoid cuckoldry by yellow-throated “sneaker” males, but mate-guarding is ineffective against aggressive orange-throated neighbors. The ultradominant orange-throated males are highly polygynous and maintain large territories; they overpower blue-throated neighbors and cosire offspring with their females, but are often cuckolded by yellow-throated males. Finally, yellow-throated sneaker males sire offspring via secretive copulations and often share paternity of offspring within a female's clutch. Sneaker males sire more offspring posthumously, indicating that sperm competition may be an important component of their strategy.